Response to "Comments on 'Hydrodynamic and dispersion behavior in a non-porous silica monolith through fluid dynamic study of a computational mimic reconstructed from sub-micro-tomographic scans"' - Loh, K.-C. (2014)
10.1016/j.chroma.2013.05.077